1999
DOI: 10.1063/1.124252
|View full text |Cite
|
Sign up to set email alerts
|

Semi-insulating C-doped GaN and high-mobility AlGaN/GaN heterostructures grown by ammonia molecular beam epitaxy

Abstract: A method of growing semi-insulating GaN epilayers by ammonia molecular beam epitaxy through intentional doping with carbon is reported. Thick GaN layers of high resistivity are an important element in GaN-based heterostructure field-effect transistors. A methane ion source was used as the carbon dopant source. The cracking of the methane gas by the ion source was found to be the key to the effective incorporation of carbon. High-quality C-doped GaN layers with resistivities greater than 106 Ω cm have been grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 17 publications
0
105
1
Order By: Relevance
“…1 Another possibility to obtain high resistive GaN layers is by acceptor doping. MBE grown C-doped layers 2 and hydride vapor phse epitaxial Zn-doped layers 3 with resistivity of 10 6 and 10 12 ⍀ cm, respectively, have been reported. Unfortunately, carrier concentration and mobility data on samples with resistivity higher than 14 ⍀ cm are not present in the literature due to the use of conductive substrates, 3 or unmeasurable Hall coefficients.…”
Section: ͓S0003-6951͑00͒02825-4͔mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Another possibility to obtain high resistive GaN layers is by acceptor doping. MBE grown C-doped layers 2 and hydride vapor phse epitaxial Zn-doped layers 3 with resistivity of 10 6 and 10 12 ⍀ cm, respectively, have been reported. Unfortunately, carrier concentration and mobility data on samples with resistivity higher than 14 ⍀ cm are not present in the literature due to the use of conductive substrates, 3 or unmeasurable Hall coefficients.…”
Section: ͓S0003-6951͑00͒02825-4͔mentioning
confidence: 99%
“…High resolution x-ray diffraction measurements showed a reasonable layer quality with Х7 arc min full width at half maximum of the ͑0002͒ scan. 9 Samples of about 6ϫ6 mm 2 were cut from each wafer and In contacts were alloyed at 850°C after appropriate surface cleaning. The ohmic behavior of the contacts was confirmed by current-voltage characteristics.…”
Section: ͓S0003-6951͑00͒02825-4͔mentioning
confidence: 99%
“…A modulation-doped field-effect transistor based on the Al x Ga 1Ϫx N/GaN heterostructures has shown encouraging high-frequency, high-power, and high-temperature performance. 5 One of the major challenges in group III nitride semiconductors is the heterogeneous integration of free standing GaN-based devices with dissimilar substrates. [3][4][5][6] Direct wafer bonding has been reported to be an ideal approach to integrate mismatched materials and has been used to fabricate a number of advanced microelectronic or photonic devices.…”
Section: Interface Structure and Adhesion Of Wafer-bonded Ganõgan Andmentioning
confidence: 99%
“…5 One of the major challenges in group III nitride semiconductors is the heterogeneous integration of free standing GaN-based devices with dissimilar substrates. [3][4][5][6] Direct wafer bonding has been reported to be an ideal approach to integrate mismatched materials and has been used to fabricate a number of advanced microelectronic or photonic devices. 3,4,6,7 Wafer bonding of GaN and other related semiconductors has been reported by a few research groups, such as GaN/GaAs, 3,4 GaN/InP, 6 and GaN/GaN.…”
Section: Interface Structure and Adhesion Of Wafer-bonded Ganõgan Andmentioning
confidence: 99%
“…These deep levels are a necessary requirement for device operation since they suppress buffer leakage and short-channel effects [11]. RF devices frequently make use of Fe doping to render the GaN insulating [12] - [14], but for the higher voltages required for many power switching applications, it has been found that carbon doping delivers higher breakdown voltage and lower off-state leakage [15,16]. Unfortunately, it has also been found that using carbon can often result in significant current-collapse [10,15].…”
Section: Introductionmentioning
confidence: 99%